Care for Atrial Fibrillation and Outcomes in Rural Versus Urban Communities in the United States: A Systematic and Narrative Review - Anthony L. Lin; Kelli Allen; Jorge A. Gutierrez; Jonathan P. Piccini; Zak Loring (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Atrial fibrillation (AF) is the most common sustained arrhythmia and associated with increased morbidity and mortality. Differences have been identified between medical care delivered in urban and rural settings, and rurality‐based disparities may exist in AF care. We performed a systematic review investigating the effect of rurality on AF care and outcomes in the United States. PubMed was queried for entries on AF and rurality: (“atrial fibrillation” OR “atrial flutter”) AND (“rural” OR “urban” OR “rurality” OR “metro” OR “metropolitan”) AND (“united states” OR “US” OR “U.S.”) published up to September 24, 2023. Anticoagulation, rhythm control, settings of care, outcomes, and all‐cause mortality were reviewed in relevant studies. The search identified 395 total articles. After screening, 14 relevant articles were included in the review. These studies ranged from 1993 to 2020 and analyzed approximately 41.7 million AF patient encounters. The use of catheter ablation for AF per electrophysiologist was similar across the rural–urban spectrum. Patients with AF and rural residence were less likely to receive a direct oral anticoagulant and more likely to remain on warfarin (relative risk, 0.90 [95% CI, 0.88–0.92]). Patients in rural communities were less likely to receive non‐emergent AF care (odds ratio [OR], 0.96 [95% CI, 0.93–0.98]). In‐hospital mortality for patients with AF admitted to rural hospitals was higher than urban hospitals (OR, 1.19 [95% CI, 1.01–1.39)]. Measurable differences exist in both treatments and outcomes of patients with AF between rural and urban settings in the United States. These differences should inform future investigations and strategies to improve health in people with AF.